Implementation of Government Policies in Fulfilling Workers' Rights to Employment Social Security Based on Labor Law Number 13 of 2003 - Simarmata, Regan Theola P; Hutapea, Novelina Mutiara S; Sitepu, Desy Kartika C (Pancasila and Civics Education Journal, 2025)
ABSTRACTThe development of employment in Indonesia is based on the provisions of Law Number 13 of 2003 concerning employment. Law Number 13 of 2003 is a replacement for Law Number 14 of 1969 concerning the main provisions regarding employment. The issuance of Law Number 13 of 2003 is expected to be able to answer various challenges and problems of worker protection and Indonesian Migrant Workers. Law becomes an instrument in the sustainability of national development today, national development is carried out to overcome various problems faced in government intervention efforts in the field of employment into two, namely private and public and in a scope that is regulated to be broader. The purpose of employment development itself as stated in Article 4 of Law Number 13 of 2003 is: to empower and utilize the workforce optimally and humanely. realizing equal employment opportunities and providing workers in accordance with national and regional development needs, providing protection to workers in realizing welfare, increasing the welfare of workers and their families. The objectives of writing this scientific work in the form of a thesis are: (1) to find out the form of the relationship between employers and workers, (2) to find out the legal consequences for employers who do not register themselves and workers who wish to register themselves, (3) to find out the government's efforts regarding workers' rights in obtaining social security for workersKeywords: Labor, Workers' Rights, Social Security